Entre o encenado, o visto e o escrito : o silêncio : escuta do diário de Frida Kahlo - Del Maestro, Maria da Penha Kopernick (2014)
The central corpus of this research is The Diary of Frida Kahlo, an intimate self-portrait, posthumous edition of the report made by the artist in the last ten years of his life (1944- 1954). The book is composed of a hybrid text overlapping self-portraits, colors, collages, figures and various types of writing: thoughts, poems, letters and stories of dreams, mixed with everyday alleged author. As it appears in its public version, the diary seems to be a passive interlocutor of Frida Kahlo’s thought, apparently disordered and illogical. But, for him, we can see the power and the fragility of the work and figure of the author, and the ability to resist living within your time and pass him through his artistic legacy, in which we find traces of his personal memory, indivisible of Mexican memory.From theoretical postulates about the writing itself, autobiography, diary, memory and performance, as well as on the history andculture of Mexico, we’ll try to understand how Frida Kahlo builds this hybrid form. Styling-pictorial text and interpreting it as a manifestation of the author's poetic, we will try to verify the hypothesis that, in his diary, Frida Kahlo uses performance to stage for herself and her work, mise en abyme.